2023
DOI: 10.1002/advs.202306298
|View full text |Cite
|
Sign up to set email alerts
|

BHLHE40 Inhibits Ferroptosis in Pancreatic Cancer Cells via Upregulating SREBF1

Yizhi Cao,
Xuelong Wang,
Yang Liu
et al.

Abstract: Pancreatic cancer (PCa) is one of the most fatal human malignancies. The enhanced infiltration of stromal tissue into the PCa tumor microenvironment limits the identification of key tumor‐specific transcription factors and epigenomic abnormalities in malignant epithelial cells. Integrated transcriptome and epigenetic multiomics analyses of the paired PCa organoids indicate that the basic helix‐loop‐helix transcription factor 40 (BHLHE40) is significantly upregulated in tumor samples. Increased chromatin access… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 65 publications
(64 reference statements)
0
1
0
Order By: Relevance
“…Studies revealed that ZMIZ1 was closely associated with oxidative stress, 31 while BHLH40 mediated lipid peroxidation, a classical feature of ferroptosis. 32 This suggests that injured renal tubular epithelial cells may activate ZMIZ1 and BHLH40 to promote GCLC expression after renal injury. However, further mechanistic studies are necessary to obtain definitive evidence.…”
Section: Discussionmentioning
confidence: 99%
“…Studies revealed that ZMIZ1 was closely associated with oxidative stress, 31 while BHLH40 mediated lipid peroxidation, a classical feature of ferroptosis. 32 This suggests that injured renal tubular epithelial cells may activate ZMIZ1 and BHLH40 to promote GCLC expression after renal injury. However, further mechanistic studies are necessary to obtain definitive evidence.…”
Section: Discussionmentioning
confidence: 99%